Partially replacing cyclophosphamide with bendamustine in combination with cyclosporine A improves survival and reduces xenogeneic graft-versus-host-disease - Gilman, Kristy E.; Cracchiolo, Megan J.; Matiatos, Andrew P.; Davini, Dan W.; Simpson, Richard J.; Katsanis, Emmanuel (Frontiers in Immunology, 2023)
The use of allogeneic hematopoietic cell transplantation (allo-HCT) for treating hematological disorders is increasing, but the development of graft-versus-host disease (GvHD) remains a major cause of morbidity and mortality. The use of post-transplant cyclophosphamide (CY) has significantly improved outcomes following allo-HCT, but complications of viral reactivation due to delayed immune reconstitution or relapse remain. Other laboratories are evaluating the potential benefit of lowering the dose of CY given post-transplant, whereas our laboratory has been focusing on whether partially replacing CY with another DNA alkylating agent, bendamustine (BEN) may be advantageous in improving outcomes with allo-HCT. Here, we utilized a xenogeneic GvHD (xGvHD) model in which immunodeficient NSG mice are infused with human peripheral blood mononuclear cells (PBMCs). We show that a lower dose of CY (25 mg/kg) given on days +3 and +4 or CY (75 mg/kg) given on only day +3 post-PBMC infusion is not sufficient for improving survival from xGvHD, but can be improved with the addition of BEN (15 mg/kg) on day +4 to day +3 CY (75 mg/kg). CY/BEN treated mice when combined with cyclosporine A (CSA) (10mg/kg daily from days +5 to +18 and thrice weekly thereafter), had improved outcomes over CY/CY +CSA treated mice. Infiltration of GvHD target organs was reduced in both CY/CY and CY/BEN treatment groups versus those receiving no treatment. CY/CY +CSA mice exhibited more severe xGvHD at day 10, marked by decreased serum albumin and increased intestinal permeability. CY/BEN treated mice had reductions in naïve, effector memory and Th17 polarized T cells. RNAseq analysis of splenocytes isolated from CY/CY and CY/BEN treated animals revealed increased gene set enrichment in multiple KEGG pathways related to cell migration, proliferation/differentiation, and inflammatory pathways, among others with CY/BEN treatment. Together, we illustrate that the use of CY/BEN is safe and shows similar control of xGvHD to CY/CY, but when combined with CSA, survival with CY/BEN is significantly prolonged compared to CY/CY.